Aggregatibacter actinomycetemcomitans sensitivity towards chlorophyll of Moringa leaf after activated by diode laser - I Gde Bagus Yatna Wibawa; Suryani Diah Astuti; Ernie Maduratna Setiawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Regular brushing teeth with scaling and root planning (SRP) cannot effectively decrease the periopatogen bacterial colonies. Even with the addition of antibiotics to support SRP, such as tetracycline given with low doses and for a long time may cause bacteria to become resistant and the effectiveness to eliminate colonies of bacteria being reduced. Photodynamic is a treatment modality that does not cause resistance and potentially to eliminate the growth of bacterial colonies. Moringa oleifera is a plant that can be easily found in Indonesia, by extracting chlorophyll of Moringa oleifera leaves, it can be used as a photosensitizer agent to increase the absorption of light on photodynamic method. Purpose: This study aimed to determine the potential photodynamic inactivation therapy to inactivate (eliminate) periopatogen bacterium. Method: This study used Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans). Laser diode 660nm as a light source with 8mm optical fiber to guide the beam, also used 20% extract chlorophyll of Moringa oleifera leaf as photosensitizer. Four diode lasers energy density exposures (2,5J.cm-2, 5J.cm-2, 7,5J.cm-2, and 10J.cm-2) are used from both at the in vitro photodynamic inactivation test. Result: The highest percentage of deaths occurred in the group treated with addition of photosensitizer and exposed by 660 nm diode laser with 10J.cm-2 energy density, which is 83.01%, compared to the results obtained in the group without addition of the photosensitizer. Conclusion: Chlorophyll of Moringa oleifera leaf after activated by diode laser effectively eliminates A. actinomycetemcomitans.